2021
DOI: 10.28992/ijsam.v5i1.338
|View full text |Cite
|
Sign up to set email alerts
|

Does CSR Expenditure and Sustainability Reporting Improve Firm Performance? Mandatory CSR Regimes in India

Abstract: This paper aims to investigate whether firms that comply with corporate social responsibility (CSR) expenditure and undertake voluntary sustainability reporting will have lower systematic risk and higher stock returns—the proxies for measuring firm performance—in mandatory CSR regimes in India. The instrumental approach of stakeholder theory asserts that firms considering stakeholders’ interests, including societal interest, are likely to show better firm performance compared to others. Therefore, on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Aligning with these studies, Anwar and Malik (2020), concluded that the quality of information in sustainability reports is less relevant and transparent, and Burzillo et al, (2022) was unable to find evidence that sustainability report provide significant information for investors decision making Despite the mix findings of the consequence of sustainability reporting practices on stakeholders attitudes, the introduction of sustainability reporting is an important communication tool (Axjonov , 2018) for organizations to disclose information on their governance issues and outcomes, and to communicate the value about their activities (Higgins et al, 2020;KPMG, 2022). Providing stakeholders information about organization activities demonstrates commitment to the interests of the society and various stakeholders (Garg & Gupta, 2021). The information provided for society is in efforts to mitigate adverse effects on the environment and society (Akisik and Gal, 2019), while the information for investors serves as a to gauge credit risk and consequently shareholder returns (García-Sánchez and NogueraGámez, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Aligning with these studies, Anwar and Malik (2020), concluded that the quality of information in sustainability reports is less relevant and transparent, and Burzillo et al, (2022) was unable to find evidence that sustainability report provide significant information for investors decision making Despite the mix findings of the consequence of sustainability reporting practices on stakeholders attitudes, the introduction of sustainability reporting is an important communication tool (Axjonov , 2018) for organizations to disclose information on their governance issues and outcomes, and to communicate the value about their activities (Higgins et al, 2020;KPMG, 2022). Providing stakeholders information about organization activities demonstrates commitment to the interests of the society and various stakeholders (Garg & Gupta, 2021). The information provided for society is in efforts to mitigate adverse effects on the environment and society (Akisik and Gal, 2019), while the information for investors serves as a to gauge credit risk and consequently shareholder returns (García-Sánchez and NogueraGámez, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan penelitian lainnya berpendapat bahwa Pelaksanaan CSR akan meningkatkan nilai perusahaan dilihat dari harga saham dan laba perusahaan (earning) sebagai akibat dari para investor yang menanamkan saham diperusahaan (Febriansyah et al, 2021). Hubungan positif antara pengeluaran CSR wajib dan kinerja perusahaan berubah menjadi negatif jika pelaporan keberlanjutan sukarela menyiratkan bahwa inisiatif keberlanjutan memerlukan biaya yang lebih tinggi daripada manfaat yang diterima dari inisiatif tersebut (Garg & Gupta, 2021).…”
Section: Pendahuluanunclassified